The Cognitive Use of Prior Knowledge in Design Cognition: The Role of Types and Precedents in Architectural Design - Zeynep Cigdem Uysal Urey (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
This paper examines the cognitive use of prior knowledge in the design and evaluates the role of types and precedents in architectural design and education from a cognitive perspective. The previous research on design cognition shows that the amount of prior knowledge possessed by the designer plays a fundamental role in the production and quality of the creative outcome. This paper examines this correlation between the cognitive concept of cultural schemas with the architectural concept of types and investigates the cognitive role of types and precedents within architectural design and education in the light of the cognitive literature. With such an attempt, the research conducts an interdisciplinary theoretical inquiry that respectively studies the role of prior knowledge in design cognition, the concept of cognitive-cultural schemas, the concept of type and its relationship with cultural schemas, and the cognitive role of types and precedents in architectural design and education. In conclusion, this study proposes that types function identically as cultural schemas at the cognitive level and types and precedents have a generative value for architectural design, by virtue of the fact that they exist as the initial cognitive schemas that are employed at the beginning of the design process.